2016
DOI: 10.4172/2329-888x.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Cheese “Peulh Type”: Characterization and Sensory Aspects

Abstract: The calotropine, a vegetable coagulating enzyme, extracted from Calotropis procera is very used in the preparation of traditional Peulh cheese. In this study, the fresh leaves of this vegetable were used to coagulate raw milk for the production of the fresh cheese Peulh type which was characterized by the physicochemical and sensory aspects. The results showed that this traditional cheese presented a total dry extract of 32.49%, pH 6.28, a lactic acidity of 0.14 p.cent, a protein content of 28.30% and a sweet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
3
3
1
Order By: Relevance
“…Actual cheese yield (kg cheese /100 kg milk) result of current study was somehow in agreement with the findings of Benyahia Krid et al (2016), and it was revealed 17.69 g/100 g yield of cheese. Despite the fact that, findings of Chikpah and Teye (2015) reported that yield of soft cheeses was 203.1, 214.3, and 237.4 g/L.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Actual cheese yield (kg cheese /100 kg milk) result of current study was somehow in agreement with the findings of Benyahia Krid et al (2016), and it was revealed 17.69 g/100 g yield of cheese. Despite the fact that, findings of Chikpah and Teye (2015) reported that yield of soft cheeses was 203.1, 214.3, and 237.4 g/L.…”
Section: Resultssupporting
confidence: 92%
“…Calotropis procera leaves traditionally use as antimicrobial activity in flat bread handling in pastoral and agro‐pastoral areas of Ethiopia. The calotropine is a protease cysteine coagulant agent which plays a great role in milk‐clotting activity it presents in the C. procera plant parts (Benyahia Krid et al, 2016). Dairy food spoilage is caused by the growth of microorganisms, primarily bacteria and fungi, that convert nutrients into energy which they use for their own growth.…”
Section: Introductionmentioning
confidence: 99%
“…The study results) show a pH of 6.38, relatively close to the pH 6.28 given by Benyahia-Krid et al, (2016) [9] for the "peulh" cheese type prepared from the coagulation of milk by the filtrate of Calotropis procera leaves. However, Necib & Tabet (2018) [33] give an average pH of 5.89 for fresh cheese prepared from Pergularia tomentosa latex.…”
Section: Physico-chemical Characteristics Of Manufactured Fresh Cheesesupporting
confidence: 87%
“…Necib & Tabet (2018) [33] present fresh cheese yields of 15.35% for cheese obtained by Pergularia tomentosa latex milk coagulation and 15.27% for that obtained by Pergularia tomentosa leaves filtrate milk coagulation. On the other hand, Benyahia-Krid (2016) [9], have presented a cheese yield on a fresh basis of 17.69% and on a dry basis of 55.45% for the Peulh type fresh cheese obtained by calotropaïn milk coagulation of Calotropis procera. For this same last plant and for the same Peulh type fresh cheese, Djeddi & Misky (2014) [29] noted a cheese yield of 7.69%, and Chella & Mamou (2018) [43] of 24.9%.…”
Section: Physico-chemical Characteristics Of Manufactured Fresh Cheesementioning
confidence: 99%
See 1 more Smart Citation